Surface‐Enforced Alignment of Reprogrammable Liquid Crystalline Elastomers - Hebner, Tayler S.; Kirkpatrick, Bruce E.; Anseth, Kristi S.; Bowman, Christopher N.; White, Timothy J. (Advanced science, 2022)
Liquid crystalline elastomers (LCEs) are stimuli‐responsive materials capable of undergoing large deformations. The thermomechanical response of LCEs is attributable to the coupling of polymer network properties and disruption of order between liquid crystalline mesogens. Complex deformations have been realized in LCEs by either programming the nematic director via surface‐enforced alignment or localized mechanical deformation in materials incorporating dynamic covalent chemistries. Here, the preparation of LCEs via thiol‐Michael addition reaction is reported that are amenable to surface‐enforced alignment. Afforded by the thiol‐Michael addition reaction, dynamic covalent bonds are uniquely incorporated in chemistries subject to surface‐enforce alignment. Accordingly, LCEs prepared with complex director profiles are able to be programmed and reprogrammed by (re)activating the dynamic covalent chemistry to realize distinctive shape transformations. Complex actuation of liquid crystalline elastomers (LCEs) is realized in a distinctive materials chemistry that is amenable to surface‐enforced alignment that incorporates dynamic covalent chemistry. LCEs are first programmed via surface patterning and subsequently (re)programmed by dynamic bond exchange. The incorporation of dynamic bonds is enabled by the use of thiol‐Michael oligomerization.